(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article presents practical suggestions and analyzes of current problems related to the promotion of our national musical heritage, music education, and their solutions. In addition, the article emphasizes the reforms implemented by our state in the direction of the development of the industry